Accelerating the convergence of the iterative methods of interpolatory type - Păvăloiu, Ion (Rev. Anal. Numér. Théor. Approx., 2005)
In this paper we deal with iterative methods of interpolatory type, for solving nonlinear equations in Banach spaces. We show that the convergence order of the iterations may considerably grow if the nodes are properly controlled.